P3.123 Hepatitis C Testing and Incidence in HIV-Positive Men Who Have Sex with Men in Melbourne, Victoria. A Retrospective Cohort Study. (13th July 2013) - Lim, M S C; Hellard, M; El-Hayek, C; Cuevas, M; Fairley, C; Leslie, D; Roth, N; Tee, B; Stoove, M
Abstract : Background: Over the past five years there have been increasing reports of HCV transmission in HIV-positive men who have sex with men (MSM) globally. It is unclear whether this increase is due to increased transmission or increased detection (due to increased testing). This paper investigated reasons for increased HCV notification in HIV-positive MSM. Methods: HIV viral load test records between April 2006 and December 2011 were used to identify all HIV-positive patients attending three high MSM caseload clinics in Melbourne, Victoria. Their HCV test records were retrospectively linked over the same period. The following were determined: frequency of HCV testing; proportion of HIV-positive men tested for HCV annually; and HCV prevalence and incidence rate (per 100PY). Poisson regression calculated trends over time. Results: 3007 HIV-positive men attended the clinics; 2190 (73%) were tested for HCV at least once, with 250 (11.4%) testing HCV positive over the study period. The prevalence of co-infection declined significantly from 11.9% in 2006 to 7.4% in 2011 (p = 0.01). The number of HIV-positive men tested for HCV increased each year although the proportion tested remained the same (approximately 75%) and testing frequency did not change (average 1.4 test/person/year). 187 HIV-positive men were identified with HCV on their initial test and 63 incident infections were observed. HCV incidence among HIV-positive men was 1.55/100PY with no significant change over the study period. Conclusions: We found that HCV incidence in HIV-positive MSM remained stable and that prevalence decreased in HIV-positive MSM throughout the study period. Our results suggest the increase in HCV case notifications among HIV-positive men may be explained by an overall increase in HCV testing in this population. The steady increase in the number of HIV-positive MSM who remain well and consequently routinely tested for HCV may be contributing the increase in HCV notifications.